METODOLOGI QIYAS DALAM ISTINBATH HUKUM ISLAM - arief hidayat tumanggor (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
Shariah is the concrete embodiment in the middle of the community.”Even so, the Shari'ah as puts the teachings of Islam grew in a variety of situations, conditions and aspects of spacetime.” The ontological reality of Shari'ah is then gave birth to the epistemology of Islamic law (fiqh) which is basically a remotely and called the scholars with a social fact enclosing them.”These historical facts show that Islamic law (fiqh) justification of the plurality of the formulation of the law due to the role of epistemology